THE EFFECT OF STRATEGIC RELATIONSHIP ON BUSINESS VALUE - handry sudiartha athar (STIE Malangkucecwara, 2022)
The purpose of this study was to determine the effect of strategic relationships on business value in the dry tobacco leaf industry in West Nusa Tenggara, Indonesia. This study takes an economic approach, especially management sciences with a focus on strategic management. This research is descriptive and verification. Data collection techniques used were questionnaires and observations. The results showed that strategic relationships have a positive and significant effect on business value. This means that the better the application of strategic relationships, the better the business value of the dry tobacco leaf industry in West Nusa Tenggara, Indonesia.